2003
DOI: 10.1038/sj.onc.1206947
|View full text |Cite
|
Sign up to set email alerts
|

Vaults: a ribonucleoprotein particle involved in drug resistance?

Abstract: Vaults are ribonucleoprotein particles found in the cytoplasm of eucaryotic cells. The 13 MDa particles are composed of multiple copies of three proteins: an M(r) 100 000 major vault protein (MVP) and two minor vault proteins of M(r) 193 000 (vault poly-(ADP-ribose) polymerase) and M(r) 240 000 (telomerase-associated protein 1), as well as small untranslated RNA molecules of approximately 100 bases. Although the existence of vaults was first reported in the mid-1980s no function has yet been attributed to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
180
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 92 publications
(135 reference statements)
4
180
0
1
Order By: Relevance
“…PTEN binds to MVP, a protein hypothesized to be a general carrier molecule for nuclear-cytoplasmic transport (Mossink et al, 2003), in yeast two-hybrid screens (Yu et al, 2002). Further analysis confirmed that this interaction occurs in both 293T and HeLa cells and localized the binding sites to the C2 domain of PTEN and the EF-hand pair (a calcium-binding motif) of MVP.…”
Section: Nuclear Ptenmentioning
confidence: 61%
“…PTEN binds to MVP, a protein hypothesized to be a general carrier molecule for nuclear-cytoplasmic transport (Mossink et al, 2003), in yeast two-hybrid screens (Yu et al, 2002). Further analysis confirmed that this interaction occurs in both 293T and HeLa cells and localized the binding sites to the C2 domain of PTEN and the EF-hand pair (a calcium-binding motif) of MVP.…”
Section: Nuclear Ptenmentioning
confidence: 61%
“…Multidrug-resistant cell lines have been shown to use these routes to gain resistance to various drugs. The expected role of vaults in MDR is supported by the following evidence: (a) vaults and their components are upregulated in cells treated with cytotoxic compounds (6), (b) vaults are involved in nucleocytoplasmic transport (2,17), and (c) compounds that interact with the vaults (17). Despite these findings, until recently (18), the vault components were not shown to interact directly with chemotherapeutic compounds.…”
Section: Introductionmentioning
confidence: 79%
“…YB-1 has also been shown to induce basal and 5-fluorouracil-induced expression of the major vault protein (MVP/LRP) gene, the promoter of which contains a Ybox (Stein et al, 2005). In human malignancies, vault proteins are involved in acquiring drug resistance (Mossink et al, 2003). Taken together, these findings suggest that nuclear localization of YB-1 might play a key role in the acquisition of global drug resistance through transcriptional activation of relevant genes and the repair of damaged DNA (Kuwano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%